Effective duration of gas nitriding process on AISI 316L for the formation of a desired thickness of surface nitrided layer - Mahmoud, H.R.S. (EDP Sciences, 2014)
High temperature gas nitriding performed on AISI 316L at the temperature of 1200Â°C. The microstructure of treated AISI 316L samples were observed to identify the formation of the microstructure of nitrided surface layer. The grain size of austenite tends to be enlarged when the nitriding time increases, but the austenite single phase structure is maintained even after the long-time solution nitriding. Using microhardness testing, the hardness values drop to the center of the samples. The increase in surface hardness is due to the high nitrogen concentration at or near the surface. At 245HV, the graph of the effective duration of nitriding process was plotted to achieve the maximum depth of nitrogen diffuse under the surface. Using Sigma Plot software best fit lines of the experimental result found and plotted to find out effective duration of nitriding equation as Y=1.9491(1-0.7947x), where Y is the thickness of nitrided layer below the surface and X is duration of nitriding process. Based on this equation, the duration of gas nitriding process can be estimated to produce desired thickness of nitrided layer. Â© 2014 Owned by the authors, published by EDP Sciences.